2017
DOI: 10.1104/pp.17.00439
|View full text |Cite
|
Sign up to set email alerts
|

Cytological and Transcriptomic Analyses Reveal Important Roles of CLE19 in Pollen Exine Formation

Abstract: The CLAVATA3/ESR-RELATED (CLE) peptide signals are required for cell-cell communication in several plant growth and developmental processes. However, little is known regarding the possible functions of the CLEs in the anther. Here, we show that a T-DNA insertional mutant, and dominant-negative (DN) and overexpression (OX) transgenic plants of the CLE19 gene, exhibited significantly reduced anther size and pollen grain number and abnormal pollen wall formation in Arabidopsis (Arabidopsis thaliana). Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 76 publications
1
15
0
1
Order By: Relevance
“…None of the 24 MADS_II genes had a simple 1:1 ortholog in Arabidopsis, suggesting that some wheat orthologs function in flowering (those within modules 8 and 11), whereas others could have developed different functions, despite being phylogenetically closely related. Thus, these data provide a framework to identify and prioritize the most likely functional orthologs of known model system genes within polyploid wheat, to characterize them functionally (38), and to dissect genetic factors controlling important agronomic traits (39,40). A more detailed analysis of tissue-specific and stress-related networks (23) provides a framework for defining quantitative variation and interactions between homeologs for many agronomic traits (41).…”
Section: Atlas Of Transcription Reveals Traitassociated Gene Co-regul...mentioning
confidence: 99%
“…None of the 24 MADS_II genes had a simple 1:1 ortholog in Arabidopsis, suggesting that some wheat orthologs function in flowering (those within modules 8 and 11), whereas others could have developed different functions, despite being phylogenetically closely related. Thus, these data provide a framework to identify and prioritize the most likely functional orthologs of known model system genes within polyploid wheat, to characterize them functionally (38), and to dissect genetic factors controlling important agronomic traits (39,40). A more detailed analysis of tissue-specific and stress-related networks (23) provides a framework for defining quantitative variation and interactions between homeologs for many agronomic traits (41).…”
Section: Atlas Of Transcription Reveals Traitassociated Gene Co-regul...mentioning
confidence: 99%
“…It has a role in enabling the CLE peptide to rotate or bend [6]. Previous research has also shown that a glycine-to-threonine substitution at residue 6 gave the strongest antagonistic effect in the wild type [30]. In addition, the CLE domain also showed high conservation at residues 1, 4, 5, 9 and 11 in wheat, rice and Arabidopsis , and the residues are critical for the function of endogenous CLV3 in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%
“…AtCLE45 regulates both root protophloem and pollen development [24,29]. AtCLE19, apart from its role in controlling the root meristem, regulates cotyledon establishment, endosperm development and pollen-wall formation in Arabidopsis [30,31]. Tracheary Element Differentiation Inhibitory Factor (TDIF), a CLE-like peptide, was originally isolated as a suppressor of tracheary-element differentiation from the Zinnia elegans mesophyll cell-culture medium.…”
Section: Introductionmentioning
confidence: 99%
“…For callose examination, tetrads were dissected from the anthers and stained with 0.01% (w/v) of aniline blue as described previously ( Lu et al, 2014 ). Semi-thin sections of anthers from the flowers of mutants, RNAi lines, and the wild type were fixed overnight in FAA (50% of ethanol, 5.0% of glacial acid, and 3.7% of formaldehyde), dehydrated in a graded ethanol series (2 × 50, 70, 85, 95, 2 × 100%), and then embedded in Technovit 7100 resin (Heraeus Kulzer) as previously described ( Zhang et al, 2007 ; Wang et al, 2017 ). The embedded tissues were sectioned (1μm thick) using a motorized RM2265 rotary microtome (Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%